1997
DOI: 10.1074/jbc.272.11.7069
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Modulates Ryanodine Receptor from Skeletal Muscle Sarcoplasmic Reticulum

Abstract: In this report, we demonstrate the ability of the cellular thiol glutathione to modulate the ryanodine receptor from skeletal muscle sarcoplasmic reticulum. In muscle cells, cytosolic Ca 2ϩ levels are regulated by the intramuscular organelle, the sarcoplasmic reticulum (SR) 1 (1-3). Following the arrival of an action potential at the surface membrane and subsequent depolarization of the transverse tubule, the SR releases its lumenal store of Ca 2ϩ through the Ca 2ϩ release channel (CRC)/ryanodine receptor (Ry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(87 citation statements)
references
References 29 publications
6
81
0
Order By: Relevance
“…The Scatchard analysis was based on a one-site model [5]. From the plot of the ratio of bound to free ryanodine (B\F ) against B, K d (the equilibrium binding constant) and B max (the maximal number of ryanodine-binding sites) were estimated from the equation B\F l (B max kB)\K d .…”
Section: Scatchard Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…The Scatchard analysis was based on a one-site model [5]. From the plot of the ratio of bound to free ryanodine (B\F ) against B, K d (the equilibrium binding constant) and B max (the maximal number of ryanodine-binding sites) were estimated from the equation B\F l (B max kB)\K d .…”
Section: Scatchard Analysismentioning
confidence: 99%
“…It has been shown that the function of RyR1s can be modulated by various endogenous and exogenous factors, including caffeine, Mg# + and adenine nucleotide [2][3][4][5]. It is thought that caffeine increases the apparent affinity of the activation site for Ca# + , whereas Mg# + inhibits ryanodine binding by competing with Ca# + for the Ca# + activation site [3,4].…”
Section: Interaction Of the Effects Of Zn 2 + And Other Ryr Modulatorsmentioning
confidence: 99%
See 3 more Smart Citations